2000
DOI: 10.1046/j.1365-2923.2000.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the concepts of confidence and competence to produce appropriate self-evaluation measurement scales

Abstract: The authors suggest that the process of assessing oneself is complicated, and by its very nature can never be objective or free from the beliefs and values individuals hold about themselves. Therefore self-evaluation instruments are best used to help individuals analyse their work practices and to promote reflection on performance. They should not be used to judge the 'accuracy' of the individual's evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 23 publications
9
156
2
1
Order By: Relevance
“…5 MAR 13 2010 221 in providing oral health care for patients is considered to be an important educational outcome. 11 There is now an overwhelming body of evidence to support the educational value of student placements in primary care settings outside the 'traditional' settings of dental schools. 12,13 Randomised controlled trials, conducted in Sheffi eld, revealed that outreach training signifi cantly improved students' ability in treatment planning and perceived clinical confi dence.…”
Section: N B R I E F Educationmentioning
confidence: 99%
“…5 MAR 13 2010 221 in providing oral health care for patients is considered to be an important educational outcome. 11 There is now an overwhelming body of evidence to support the educational value of student placements in primary care settings outside the 'traditional' settings of dental schools. 12,13 Randomised controlled trials, conducted in Sheffi eld, revealed that outreach training signifi cantly improved students' ability in treatment planning and perceived clinical confi dence.…”
Section: N B R I E F Educationmentioning
confidence: 99%
“…Doctors, like other professionals, have an obligation to update their knowledge and skills throughout their careers in order to provide the best care possible to their patients. Reflection is one way that physicians can evaluate what they know and do not know, and they can mitigate gaps in their knowledge by applying self-directed lifelong learning practices (Izatt, 2007;Mazmanian & Davis, 2002;Stewart, O'Halloran, Barton, Singleton, Harrigan & Spencer, 2003). While reflection is seen as one way to mitigate gaps in knowledge and create lifelong, self-directed physician learners, little is known about how to cultivate reflective practice skills in physicians.…”
Section: Medical Education and Reflective Learningmentioning
confidence: 99%
“…Reflection helps physicians find gaps in their knowledge and attend to their learning needs to meet the ever changing realities of medicine (Westberg & Hilliard, 2001). In her 2003 article outlining ways to strive for excellence in medical practice, Plack (2005) Therefore, one possibility to aid physicians in becoming safer practitioners is to teach them how to reflect so they can better identify their limitations and learning needs (Stewart, O'Halloran, Barton, Singleton, Harrigan & Spencer, 2003).…”
Section: Reflection In Healthcarementioning
confidence: 99%
“…Stewart et al (2000) explored the beliefs of house officers about their competence, and concluded that 'they made assessments about their competence from the lack of negative comments made by others'. It appears that neither group of students made negative comments to each other.…”
Section: Feedback From Third and Fourth Year Students Themes -Value Amentioning
confidence: 99%